(Invited) Ultrawide Bandgap β-Ga2O3 Thin Films: Growths, Properties and Devices. (17th August 2017) - Rafique, Subrina; Han, Lu; Zhao, Hongping
Abstract : Ultrawide bandgap β-Ga2 O3 represents an emerging semiconducting material for high power electronics and short wavelength optoelectronics applications. It possesses a wide band gap of 4.5-4.9 eV, and excellent chemical and thermal stability up to 1400 o C, which opens up new opportunities for various device applications. This paper reviews recent progresses on β-Ga2 O3 thin film growths, properties and device demonstrations. Methods that have been demonstrated to enable high quality β-Ga2 O3 thin film growth with controllable doping are discussed. Device applications of monoclinic β-Ga2 O3 are also covered. Finally, a conclusion and future perspectives of the research in the area of this important semiconducting material will be given.